(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The investigation of the influence of pH on the fluorescence spectra of bovine liver arginase in solutions has shown that in the region of pH 6.5–9.8, where the enzyme keeps the activity, small conformational changes take place. At the extremal pH values (2.8 and 10.5) and in the presence of high concentrations of urea the intensivity of fluorescence decreases and maximum spectra are shifted. The data suggested that polypeptide chain of arginase is damaged in 8A/ urea solutions without any cleavage of disulfide bonds.